The views and experiences of integrated care system commissioners about the adoption and implementation of virtual wards in England: qualitative exploration study - McGowan, Laura J.; Graham, Fiona; Lecouturier, Jan; Goffe, Louis; Echevarria, Carlos; Kelly, Michael P.; Sniehotta, Falko F. (Journal of medical internet research, 2024)
Background: Virtual wards (VWs) are being introduced within the National Health Service (NHS) in England as a new way of delivering care to patients who would otherwise be hospitalized. Using digital technologies, patients can receive acute care, remote monitoring, and treatment in their homes. Integrated care system commissioners are employees involved in the planning of, agreeing to, and monitoring of services within NHS England and have an important role in the adoption and implementation of VWs in clinical practice. - Objective: This study aims to develop an understanding of the acceptability and feasibility of adopting and implementing VWs in England from integrated care system commissioners’ perspectives, including the identification of barriers and facilitators to implementation. - Methods: Qualitative semistructured interviews were conducted with 20 commissioners employed by NHS England (NHSE) in various geographic regions of England. Thematic analysis was conducted, structured using the framework approach, and informed by the Consolidated Framework for Implementation Research. The COREQ (Consolidated Criteria for Reporting Qualitative Research) guidelines were followed. - Results: Four overarching themes were identified reflecting the acceptability and feasibility of key adoption and implementation processes: (1) assessing the need for VWs, (2) coordinating a system approach, (3) agreeing to Program Outcomes: NHSE Versus Organizational Goals, and (4) planning and adapting services. Commissioners expressed the need for system-level change in care provision within the NHS, with VWs perceived as a promising model that could reform patient-centered care. However, there was uncertainty over the financial sustainability of VWs, with questions raised as to whether they would be funded by the closure of hospital beds. There was also uncertainty over the extent to which VWs should be technology-enabled, and the specific ways technology may enhance condition-specific pathways. Differing interpretations of the NHSE instructions between different health care sectors and a lack of clarity in definitions, as well as use of hospital-centric language within national guidance, were considered hindrances to convening a system approach. Furthermore, narrow parameters of success measures in terms of goals and outcomes of VWs, unrealistic timescales for planning and delivery, lack of interoperability of technology and time-consuming procurement procedures, liability concerns, and patient suitability for technology-enabled home-based care were identified as barriers to implementation. Motivated and passionate clinical leads were considered key to successful implementation. - Conclusions: VWs have the potential to reform patient-centered care in England and were considered a promising approach by commissioners in this study. However, there should be greater clarity over definitions and specifications for technology enablement and evidence provided about how technology can enhance patient care. The use of less hospital-centric language, a greater focus on patient-centered measures of success, and more time allowance to ensure the development of technology-enabled VW services that meet the needs of patients and staff could enhance adoption and implementation.
Online veröffentlicht: 17. Januar, 2024
Gesehen am 22.04.2025